Alternatif Pra Rancangan Instalasi Pengolahan Air Limbah (Ipal) Industri Rumah Potong Hewan (Studi kasus rumah potong hewan Giwangan, Umbulharjo, Yogyakarta) - Sri Hastutiningrum; Hadi Prasetyo Suseno; Anggita Ratnasari (Seminar Nasional Teknik Kimia Kejuangan, 2017)
The waste water treatment at slaughterhouse is very important as the effort for reducing the consentration of the waste water pollutant to the environment. The purpose of this study is to determine the system and design tocalculate the dimension of the waste water treatment plant (WWTP) in Giwangan slaughterhouse as a case study and to calculate its construction cost. The waste water treatment plant in Giwangan slaughterhouse use a biological treatment without standard operation. In the first stage, the research was conducted by calculating the water discharge and was tested the wastewater parameters (such as BOD, COD, TSS, N-Ammonia, Lipid and pH). After the data were collected, the system was determined. Then in the last stage, dimension and construction cost are calculated. The alternatives of pre redesign for Giwangan slaughterhouse WWTP system consist of bar screen, imhoff tank, preliminary sedimentation unit, anaerobic biofilter reactor, aerobic biofilter reactor, secondary sedimentation unit, bioindicator unit and sludge drying bed unit. The dimensions of these unit are imhoff tank (length = 4.6 m, width = 2.5 m, high = 4.0 m), preliminary sedimentation unit (length = 1.5 m, width = 1.3 m, high = 2.0 m), anaerobic biofilter reactor (length = 3.7; width = 2.0 m, high = 2.5 m), aerobic biofilter reactor (length = 2.0 m, width = 1.9 m, high = 2.5 m), secondary sedimentation unit (length = 1.0 m, width = 1.3 m, high = 1.0 m), bioindicator unit (length = 2.0 m, width = 1.5 m, high = 1.0 m) and 3 unit of sludge drying bed unit (length = 1.0 m, width = 1.0 m, high = 1.0 m). The total budget required for construction was Rp 717.129.718,10.